Low-molecular-weight heparin in the acute and long-term treatment of deep vein thrombosis - Kakkar, Vijay V.; Gebska, Milena; Kadziola, Zbigniew; Saba, Neelam; Carrasco, Pilar; on behalf of the Bemiparin Investigators (Thrombosis and Haemostasis, 2003)
Low molecular weight heparins (LMWHs) are frequently used during acute treatment of deep vein thrombosis, but their utility for long-term treatment needs to be defined.In this multi-centre trial, 378 patients with acute deep vein thrombosis were randomised to intravenous unfractionated heparin (group A), once daily subcutaneous LMWH (bemiparin) for one week (group B) or once daily bemiparin in a therapeutic dose for one week followed by a maintenance dose for 12 weeks (group C).Fifty-two per cent of patients in group A, 72% of group B and 72% of group C showed venographic reduction in thrombus size assessed objectively on day 14; 20% greater improvement in group B and C indicates not only non-inferiority of bemiparin (p = 0.00003) but also superiority (p = 0.004) compared to UFH. Day 84 venographic or Doppler sonographic recanalisation of the affected veins was demonstrated in 75.3%, 79.8% and 81.5% in groups A, B and C respectively. Mortality, recurrent thromboembolic events and bleeding were similar in the three groups.Both bemiparin regimens were more effective than UFH in reducing thrombus size during the acute phase of treatment. The efficacy in terms of recurrence of venous thromboembolism and safety of Bemiparin is similar to UFH. Bemiparin is also an effective alternative to warfarin for long-term treatment.
Keywords: Heparin; deep vein thrombosis; treatment